2017
DOI: 10.1371/journal.pone.0187000
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic heterogeneity in modeling cancer evolution

Abstract: The unwelcome evolution of malignancy during cancer progression emerges through a selection process in a complex heterogeneous population structure. In the present work, we investigate evolutionary dynamics in a phenotypically heterogeneous population of stem cells (SCs) and their associated progenitors. The fate of a malignant mutation is determined not only by overall stem cell and non-stem cell growth rates but also differentiation and dedifferentiation rates. We investigate the effect of such a complex pop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 86 publications
(134 reference statements)
0
11
1
Order By: Relevance
“…He showed that in the presence of non-linear feedback, de-differentiation can lower the rates of tumor initiation and progression. Interestingly, this prediction is opposite to the prediction by Shirayeh et al [32], in which they showed that de-differentiation can increase the rate of tumor initiation in the absence of non-linear feedback. The discrepancy between these two predictions actually reveals the complexities brought by the non-linear feedback which deserves special attention in future study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…He showed that in the presence of non-linear feedback, de-differentiation can lower the rates of tumor initiation and progression. Interestingly, this prediction is opposite to the prediction by Shirayeh et al [32], in which they showed that de-differentiation can increase the rate of tumor initiation in the absence of non-linear feedback. The discrepancy between these two predictions actually reveals the complexities brought by the non-linear feedback which deserves special attention in future study.…”
Section: Discussioncontrasting
confidence: 80%
“…Previous work has e.g. considered how de-differentiation influences the waiting time to carcinogenesis [31], the fixation probability of a mutant [32, 33], the phenotypic equilibrium [3436], transient overshoots [37, 38], and radiation sensitivity [29]. However, the adaptive significance of de-differentiation is still poorly understood: Under which circumstances would de-differentiation arise in the first place and rise in abundance?…”
Section: Introductionmentioning
confidence: 99%
“…is the displacement on z i because of reaction j. Because of the linearizations (12), the stationary values of the second order moments equations provided by (24) are the solutions of a linear system, whose formal expression is achieved according to straighforward, though cumbersome computations, and is not here reported. The order of the system, by properly exploiting the simmetries, is:…”
Section: First-order Moment Equationsmentioning
confidence: 99%
“…Fluctuations in growth rate are known to be responsible for phenotypic heterogeneity, although the mechanisms behind them are still matter of investigation [19], [20]. A large effort has been spent to investigate such phenotypic heterogeneity since it is supposed to be involved in cellular growth control and cancer initiation (see [12] and references therein). Within this framework, metabolism has recently gained interest since the intrinsic noise in gene expression and enzymes accumulation has been shown to propagate to growth rate fluctuations through metabolic fluxes, according to singlecell experiments [9], [13], [22].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, special attention has been paid to the effect of de-differentiation on the cellular hierarchy by mathematical modeling of their impact. Previous works have considered how de-differentiation influences the waiting time to carcinogenesis [30], the fixation probability of a mutant [31,32], the phenotypic equilibrium [33][34][35], transient overshoots [36,37], and radiation sensitivity [29]. However, the adaptive significance of de-differentiation is still poorly understood: Under which circumstances would de-differentiation arise in the first place and rise in abundance?…”
Section: Introductionmentioning
confidence: 99%